Evaluación de la respuesta inmune de pollos COBB 500 a diferentes horas de nacimiento - Demera Rivadeneira, Anatolia (2024)
The immune response of Cobb 500 chickens was evaluated at different times of birth. The field work was carried out in the Teaching, Research and Linkage Unit UDIV Incubator Plant of the ESPAM MEFL and the experimental part in the Animalab Laboratory, the experiment was framed under a completely randomized block design with four treatments that consisted according to the time of birth T1 486 h, T2 492 h, T3 498 h, and T4 504 h distributed in both sexes. Maternal antibody levels were examined on the day of birth and vaccination levels on day 21 of life. The results show for maternal antibodies that there was no statistically significant difference (p > 0.05), on the other hand, the maternal antibodies for Newcastle and Gumboro have no correlation with the incubation hours, values of 0.46 and 0.1 respectively, nor for the antibodies Newcastle vaccinations on day 21, but a marked numerical trend is found as the incubation hours increase, the antibodies decrease. Nor is there a correlation for Gumboro vaccine antibodies at day 21 of life despite the R value of 0.98. It is concluded that the levels of maternal and vaccine antibodies in the chicks do not differ according to the time of birth, nor is there a correlation between these variables. While, the vaccine antibody load on day 21 shows a numerical trend inversely proportional to the hours of birth only for Gumboro.